PENGARUH OBESITAS DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL - Salsabilla, Salsabilla; Bunga Najla Amelia; Anggraini, Debie (Nusantara Hasana Journal, 2024)
Background: Pregnancy obesity is weight gain in pregnant women exceeding 12-16 kg of normal body weight. This negatively impacts the overall health of pregnant women and can cause hyperglycemia, hypercholesterolemia, and hypertension. Gestational hypertension is an increase in blood pressure of 140/90 mmHg from normal after 20 weeks of pregnancy and is one of the dangerous impacts that occurs due to obesity in pregnant women which can cause death for the mother and baby. Objective: To find out how obesity can affect hypertension in pregnant women and what steps pregnant women should take to prevent obesity so they can reduce the risk of developing hypertension. Methods: The method used in this systematic literature review is PRISMA-P (Preferred Reporting Items for Systemic Review and Meta-Analysis Protocols) in 2023. Studies were collected through searches on Google Scholar, Pubmed, Connector Paper data sources from 2018-2023 . Keyword searches used the PICO-S (Population Intervention Compare Outcome-Study design) technique. Results: Of the 1,053 journals and articles searched, nine journals and articles were found that fit the literature review title category. The results of this study showed that the influence of obesity is closely related to the incidence of hypertension in pregnant women. Conclusion: It was concluded that obesity can influence the incidence of hypertension in pregnant women.